2014
DOI: 10.1177/0142723714521925
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ prelinguistic communicative acts and maternal responses: Relations to linguistic development

Abstract: Infant–parent interactions are bidirectional; therefore, it is important to understand how infants’ communicative behavior elicits variable responses from caregivers and, in turn, how infants’ behavior varies with caregivers’ responses; furthermore, how these moment-to-moment interactive behaviors relate to later language development. The current study addressed these concerns by observing 10- to 13-month-old infants’ interactions with their mothers and measuring their language outcomes when they were 15 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
85
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 67 publications
12
85
1
1
Order By: Relevance
“…The fact that infants were interacting with an unfamiliar adult neutralized the possible influence of prior caregiver-child routines and shaped interaction. Moreover, with regard to the potential effects of the use of multimodal productions on later language development, our results extend the results yielded by Murillo and Belinchón (2012) and Wu and Gros-Louis (2014) to the age of 18 months, when early production of gesture-speech combinations are found to correlate with lexical and grammatical output at that stage of development.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The fact that infants were interacting with an unfamiliar adult neutralized the possible influence of prior caregiver-child routines and shaped interaction. Moreover, with regard to the potential effects of the use of multimodal productions on later language development, our results extend the results yielded by Murillo and Belinchón (2012) and Wu and Gros-Louis (2014) to the age of 18 months, when early production of gesture-speech combinations are found to correlate with lexical and grammatical output at that stage of development.…”
Section: Discussionsupporting
confidence: 82%
“…The results showed that the use of pointing gestures at 12 months, especially when accompanied by vocalizations and directed gaze on the part of the infant, correlated positively with vocabulary development at 15 months of age. In a recent study, Wu and Gros-Louis (2014) analyzed the spontaneous interactions of 10-to 13-month-old infants with their mothers in fifty-one dyads and showed that the infants' combinations of vocalization and pointing, and especially those produced when mothers were not attending to the target event, were related to the infants' subsequent comprehension skills at 15 months. It should be noted that both of the studies mentioned above are based on the analysis of spontaneous interactions, where it is difficult to behaviorally control for two important aspects of early communicative patterns, namely, (a) the pragmatic intention or motive behind children's use of pointing gestures to comment on an event or object; and (b) the social interaction gaze patterns used by the adult during the communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although one might hypothesize that the mothers of children with HL were less likely to recognize gestures as a form of communication or that they were singularly focused on their children's spoken language development, the evidence that signing and nonsigning mothers were similarly unresponsive to the gestures of their toddlers with HL runs contrary to these hypotheses. Regardless of the reason, it appears problematic that mothers of children with HL are not fully capitalizing on the potential to provide their children with responsive feedback, given the literature documenting the positive contributions of maternal responsiveness and prelinguistic communication to the subsequent language outcomes of children with NH (Brady, Marquis, Fleming, & McLean, 2004;Goldin-Meadow et al, 2007;Masur, 1982;Wu & Gros-Louis, 2014;Yoder & Warren, 1999). Providing responsive feedback to the gestures produced by toddlers with HL may be especially important, given that their more limited use of spoken words results in caregivers having fewer opportunities to provide children with HL with contingent feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Children are particularly likely to process spoken information provided by mothers in these responses, because they relate to the focus of the child's attention and interest. Evidence supporting the importance of these responses is found in studies indicating that provision of contingent responses to children's gestures promotes increased infant gesture use (J. L. Miller & Lossia, 2013) and is positively correlated with later language outcomes for children who are TD (Goldin-Meadow et al, 2007;Masur, 1982;Wu & Gros-Louis, 2014). …”
Section: Gestural Development Of Children With Nhmentioning
confidence: 95%